Domestic Violence Based on Article 5 Letter B of Law Number 23 of 2004 as a Consideration for Judges in Deciding on Divorce: Study of the Decision of the Sukoharjo Religious Court Number 223/Pdt.G/2023/PA.Skh - Kamilah; Arif Effendi; Aditya Fajri Kurnia Pradana; Afifah Afifah (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2026)
Domestic Violence (DV) is one of the major factors that can undermine family harmony and lead to divorce. Law Number 23 of 2004 concerning the Elimination of Domestic Violence provides clear regulations regarding various forms of domestic violence, including psychological violence as stipulated in Article 5(b). This study employed an empirical juridical or socio-legal approach using qualitative descriptive analysis. Data were collected through interviews, observations, documentation, and library research. Data validity was ensured through cross-checking, member checking, cross-verification, and triangulation techniques. The findings indicate that domestic violence has not been expressly recognized as an independent ground for divorce in Religious Courts because it is not explicitly regulated in the Marriage Law or the Compilation of Islamic Law. In Decision Number 223/Pdt.G/2023/PA.Skh., the judges granted the divorce based on continuous disputes and marital disharmony under the applicable marriage law provisions, while implicitly considering the substance of psychological domestic violence under Article 5(b) of Law Number 23 of 2004 in assessing the breakdown of the marital relationship. The study recommends strengthening judicial sensitivity in identifying elements of domestic violence, improving evidentiary mechanisms for victims, enhancing inter-institutional coordination, and promoting legal reform to explicitly recognize domestic violence as a ground for divorce in order to achieve substantive justice for victims.